2023
DOI: 10.1103/physrevapplied.19.014053
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional Charge-to-Spin Conversion in Graphene/ MoTe2 van der Waals Heterostructures

Abstract: Spin-charge interconversion (SCI) is a central phenomenon to the development of spintronic devices from materials with strong spin-orbit coupling (SOC). In the case of materials with high crystal symmetry, the only allowed SCI processes are those where the spin-current, charge-current, and spin-polarization directions are orthogonal to each other. Consequently, standard SCI experiments are designed to maximize the signals arising from the SCI processes with conventional mutually orthogonal geometry. However, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 80 publications
1
6
0
Order By: Relevance
“…The pure charge-to-spin precession signal Δ R CSC with out-of-plane spin polarization (due to the SHE), plotted in Figure (g), has been obtained as follows: (1) subtracting the R NL curves between the positive ( R NL ↑ ) and negative ( R NL ↓ ) alignment of the F1 magnetization, followed by (2) an antisymmetrization of the obtained curve with respect to the magnetic field. The first step removes any initial-magnetization-independent components, such as local magnetoresistance, ordinary Hall effect, and conventional EE. , The second step eliminates the possible contribution of unconventional charge-to-spin conversion with spins polarized along y , which has been observed in some van der Waals heterostructures. The reciprocal experiment (inverse SHE) is shown in the Supporting Information Figure S11 and confirms that we are in the linear response regime. A control experiment in a reference device without CuO x as an adlayer exhibits no spin-to-charge signal (see Supporting Information Figure S10).…”
supporting
confidence: 62%
“…The pure charge-to-spin precession signal Δ R CSC with out-of-plane spin polarization (due to the SHE), plotted in Figure (g), has been obtained as follows: (1) subtracting the R NL curves between the positive ( R NL ↑ ) and negative ( R NL ↓ ) alignment of the F1 magnetization, followed by (2) an antisymmetrization of the obtained curve with respect to the magnetic field. The first step removes any initial-magnetization-independent components, such as local magnetoresistance, ordinary Hall effect, and conventional EE. , The second step eliminates the possible contribution of unconventional charge-to-spin conversion with spins polarized along y , which has been observed in some van der Waals heterostructures. The reciprocal experiment (inverse SHE) is shown in the Supporting Information Figure S11 and confirms that we are in the linear response regime. A control experiment in a reference device without CuO x as an adlayer exhibits no spin-to-charge signal (see Supporting Information Figure S10).…”
supporting
confidence: 62%
“…The "twisting" effect has been reported to significantly alter the magnetic and valleytronic properties of 2D-TMDs. [129,[152][153][154][155][156] Twisting graphene from a 2D-TMD in a 2D-TMD/graphene heterostructure can enhance the valley Zeeman and Rashba effects, [129,152] as well as the charge-to-spin conversion efficiency. [153,154] By tailoring the atomic interface between twisted bilayer graphene and WSe 2 , Lin et al showed strong electron correlation within the moiré flat band, which stabilizes insulating states at both quarter and half filling, and the spin-orbit coupling drives the Mott-like insulator into ferromagnetism.…”
Section: Concluding Remarks and Outlookmentioning
confidence: 99%
“…[129,[152][153][154][155][156] Twisting graphene from a 2D-TMD in a 2D-TMD/graphene heterostructure can enhance the valley Zeeman and Rashba effects, [129,152] as well as the charge-to-spin conversion efficiency. [153,154] By tailoring the atomic interface between twisted bilayer graphene and WSe 2 , Lin et al showed strong electron correlation within the moiré flat band, which stabilizes insulating states at both quarter and half filling, and the spin-orbit coupling drives the Mott-like insulator into ferromagnetism. [155] In addition to the magnetic proximity and charge transfer effects, twisting adds an interesting experimental knob to tune the magnetic and magneto-optic functionalities of 2D-TMDs for spintronics and valleytronics applications.…”
Section: Concluding Remarks and Outlookmentioning
confidence: 99%
“…Another important long-standing challenge is the realization of semiconducting magnets with critical temperatures above room temperature . Additionally, many 2D magnets exhibit interesting quantum phenomena such as superconductivity, spin liquid states, , and topological phases. Consequently, this class of materials presents itself as a playground for quantum phenomena and strongly correlated effects, in addition to its numerous potential applications. As a result, many studies have been devoted to high-throughput and ML approaches to discover new 2D magnets.…”
Section: Introductionmentioning
confidence: 99%